Role of oxygen on the electrical activation of B in Ge by excimer laser annealing. Issue 1 (13th December 2013) - Impellizzeri, G.; Napolitani, E.; Milazzo, R.; Boninelli, S.; Cuscunà, M.; Fisicaro, G.; La Magna, A.; Fortunato, G.; Priolo, F.; Privitera, V.
<x xml:space="preserve">Abstract</x> The electrical activation of B+ implanted at 20 keV with a fluence of 1 × 1015 cm−2 in crystalline Ge, following a laser annealing (λ = 308 nm) with multipulses (1, 3, or 10), was studied. Incomplete activation was observed for all the irradiated samples. The inactivation of B was correlated to the presence of oxygen, coming from the native germanium oxide. The formation of B–O complexes occurs during the solidification of the Ge, hampering the substitutionality and the electrical activation of the dopant. We estimated the diffusivity of oxygen in liquid Ge, ∼3 × 10−5 cm2 s−1, by fitting the experimental O concentration profiles. These studies clarify the key role played by oxygen on the electrical activation of B in Ge by laser annealing, and have to be considered for the fabrication of junctions in advanced scaled Ge‐based devices.